2020
DOI: 10.1371/journal.pone.0238447
|View full text |Cite
|
Sign up to set email alerts
|

K+ promotes the favorable effect of polyamine on gene expression better than Na+

Abstract: Background Polyamines are involved in a wide variety of biological processes including a marked effect on the structure and function of DNA. During our study on the interaction of polyamines with DNA, we found that K + enhanced in vitro gene expression in the presence of polyamine more strongly than Na +. Thus, we sought to clarify the physico-chemical mechanism underlying this marked difference between the effects of K + and Na +. Principal findings It was found that K + enhanced gene expression in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…The difference in physico-chemical properties between the shrunken state and compact state of DNA has also been recently revealed experimentally [48]. Interestingly, for experiments on in vitro gene expression, the promotion and inhibition of gene expression are observed for the shrunken state and compact globule states, respectively [39,[41][42][43][44].…”
Section: Plos Onementioning
confidence: 87%
See 1 more Smart Citation
“…The difference in physico-chemical properties between the shrunken state and compact state of DNA has also been recently revealed experimentally [48]. Interestingly, for experiments on in vitro gene expression, the promotion and inhibition of gene expression are observed for the shrunken state and compact globule states, respectively [39,[41][42][43][44].…”
Section: Plos Onementioning
confidence: 87%
“…Recently, it was found that, through in vitro experiments with cell-free gene expression assay, polyamines promote gene expression just below the concentration to induce tight compaction but inhibit gene expression completely at higher concentrations [39][40][41][42]. It was revealed that such biphasic effect of polyamines neatly concerns with transition of higher order structure of DNA molecules [39,[41][42][43][44]. It would be highly expected that such characteristic function of polyamine on the structure and function of DNA play an important role in living cellular media accompanied with microphase separation.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-free in vitro transcription/translation of Luc -gene was performed with a TnT T7 Quick Coupled Transcription/Translation System (Promega) according to the manufacturer's instructions and previous reports 9 11 . Reaction mixtures containing the reporter DNAs were incubated for 90 min at 30 °C on a Dry Thermo Unit (TAITEC, Saitama, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, cell-free gene expression systems are one of the most widely used techniques in molecular biology 1 3 . The efficiency of cell-free gene expression is known to be affected by various factors such as vector type 4 7 , DNA topology 4 7 , and reaction components 8 11 , as well as the template DNA concentration 12 14 . It is noted that there exists a longstanding controversy regarding the topological effect of supercoiling, or linking number, in circular DNAs on their genomic activity 4 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The selective uptake of DNA by dextran‐rich droplets was explored for the separation of single‐ and double‐stranded DNAs, high‐ and low‐molecular‐weight DNAs, genomic DNA from a cell lysate, and even chromosomes [15–19] . We also observed that genomic DNA and DNA hydrogels were concentrated in the dextran‐rich droplets, whereas short ssDNA were distributed in both dextran‐rich droplets and a PEG‐rich continuous phase [20–22] . We expected small ssDNA and large DNA structures would have different partitions and be separable by W/W‐droplet fractionation (Figures 1B and 1 C).…”
Section: Introductionmentioning
confidence: 91%